가동중시험 관련 공동화 현상에 대한 OpenFOAM의 예측 정확도 검증 - 배준호(J.H. Bae); 김창현(C.H. Kim); 이공희(G.H. Lee) (한국전산유체공학회지, 2018)
This paper aims to validate the accuracy of open source code OpenFOAM for prediction of IST(In-Service Test)-related cavitation in the nuclear power plant. For this objective, both sharp-edged orifice and venturi-type section that are representative components, encountered in the IST-related system flow passage, are selected. The simulations are conducted using OpenFOAM multiphase solver – interphaseChangeFoam(it uses Volume of fluid method) by implementing an extended cavitation model. The flow in a sharp-edged orifice was assumed to be steady, incompressible, isothermal and multiphase flow. On the other hand, the flow in a venturi-type section was assumed to be unsteady, incompressible, isothermal and multiphase flow. The calculated results were compared with experimental result and the predicted results with commercial CFD software, ANSYS Fluent. Through this comparative study, it is concluded that OpenFOAM may have an applicability for the qualitative prediction of IST-related cavitation in the nuclear power plant and its prediction accuracy needs to be improved in the future. KCI Citation Count: 2